Genes in skin wound healing: microRNAs 1 - Sen, Chandan K. (Henry Stewart Talks, 2014)
Types of wounds, intervention and the healing process, Molecular oxygen and its role in wound healing, Gene expression in wounds, MicroRNA: drivers of the wound healing process, The involvement of miRNA in redox regulated angiogenic response, Micromanaging vascular biology, Distribution of oxygen in the wound tissue, Altered miRNAs in response to state of tissue oxygenation, OxymiRs: oxygen-sensitive miRs influence wound closure, Ischemia and hypoxia, The reaction to hypoxia: HIF and hypoxamirs, The murine ischemic wound model, Ischemic wound impaired epithelialization and proliferation, The expression of miR-210 and E2F3 in ischemic wounds